The Global Digital Compact: Opportunities and challenges for developing countries in a fragmented digital space - Carlos María Correa; Danish; Vitor Henrique Pinto Ido; Jacquelene Mwangi; Daniel Uribe Terán (South Centre, 2023)
The adoption of a Global Digital Compact (GDC) as one of the outcomes of the Summit of the Future opens up the opportunity to address in a systematic manner issues that are of critical importance for the digital global governance. It also poses a challenge to developing countries, as most of them lack the infrastructure and capabilities to fully participate in the digital transformation. Many inequalities, including a deep digital divide, do exist and would need to be addressed by the GDC for it to become a real instrument of change and improvement in the living conditions and the prospects of a better future for most of the world population. This paper examines the current fragmentation in the digital governance and some of the issues raised by the proposals made by the UN Secretary-General for adoption of the GDC.
Keywords: 300; Artificial Intelligence (AI); Common Agenda; Connectivity; Data; Data Commons; Data Protection; Digital Common Goods; Digital Cooperation; Digital Divide; Digital Economy; Digital Education; Digital Fragmentation; Digital Governance; Digital Inclusion; Digital Security; Digital Transformation; Digital Trust; Emerging Technologies; Global Digital Commons; Global Digital Compact; Human Rights; Innovation; Innovation Divide; Internet; Summit of the Future; Sustainable Development Goals (SDGs); United Nations (UN); United Nations Secretary General (UNSG)